Trichoderma: beneficial fungus for sustainable agriculture - Arpitdixit (International Journal of Fungi, 2025)
As environmentally beneficial substitutes for chemical pesticides, Trichoderma species are being utilized in agriculture more and more. Disease suppression, increased plant growth, and increased tolerance to environmental stress are just a few advantages they provide. These fungi are used in a wide range of cropping systems and formulations around the world. Their use is growing worldwide, particularly in Asia and Europe. In contemporary crop management, items derived from Trichoderma are essential as sustainable approaches gain traction. Harzianolide, a compound derived from Trichoderma harzianum SQR-T037, was studied for its effects on plant growth and defense. It significantly enhanced tomato seedling growth and root development at low concentrations. The compound also activated defense-related enzymes and induced key immune genes. Treated plants showed improved resistance to Sclerotinia sclerotiorum. This highlights harzianolide’s potential as a natural growth promoter and resistance inducer in crops. Because of their various antagonistic mechanisms, Trichoderma species are efficient biocontrol agents against plant diseases. These consist of direct parasitism of other fungus, competition for nutrition, and the release of enzymes and antibiotics. They also trigger natural defensive mechanisms and encourage plant growth. Environmental factors, pathogen species, and strain type all affect efficacy. Improved biological formulations for long-term crop protection can be developed thanks to insights into these mechanisms. Plant pathogen biocontrol and industrial enzyme production are just two uses for the adaptable fungus Trichoderma species. According to recent research, they act as endophytes, promoting immunity, stress tolerance, and plant growth. Understanding the genome has helped identify important genes related to secondary metabolite synthesis, mycoparasitism, and plant interaction. Their use in agriculture stems from their capacity to alter root architecture and elicit defense responses. These developments connect fundamental biology to creative biotechnology applications in this special issue. Soil degradation and enhanced disease resistance are just two of the major health and environmental issues brought on by the overuse of chemical pesticides and fertilizers. In contemporary agriculture, the helpful soil fungus Trichoderma has become a viable and environmentally responsible substitute. It suppresses dangerous infections and promotes plant growth in a variety of ways, including as a biocontrol agent, biofertilizer, and bioremediator. It is a perfect part of organic farming and integrated pest control systems because of its capacity to promote soil health, increase nutrient uptake, and break down contaminants. Its efficacy in crop protection is further increased by its compatibility with nanotechnology. Trichoderma has a lot of potential to lessen reliance on chemicals and promote environmentally friendly farming methods. With its ability to promote plant growth, prevent disease, and clean up the environment, Trichoderma shows great promise as a multipurpose bioagent in agriculture. It functions by inducing plant defense responses, nutritional competition, mycoparasitism, and antibiosis. Its uses include biofertilizer, biocontrol agent, and bioremediator. It also contributes to the production of environmentally acceptable nanoparticles. Because of these characteristics, Trichoderma is a useful substitute for chemical inputs. Its adoption can have a major positive impact on environmentally friendly and sustainable farming methods.
Keywords: Sustainable agriculture; Trichoderma spp; biocontrol; biofertilizer; bioremediation; nanotechnology